A novel transgenic zebrafish line for red opsin expression in outer segments of photoreceptor cells. Issue 7 (23rd April 2018) - Crespo, Cátia; Soroldoni, Daniele; Knust, Elisabeth
Abstract : Background: Opsins are a group of light‐sensitive proteins present in photoreceptor cells, which convert the energy of photons into electrochemical signals, thus allowing vision. Given their relevance, we aimed to visualize the two red opsins at subcellular scale in photoreceptor cells.Results: We generated a novel Zebrafish BAC transgenic line, which express fluorescently tagged, full‐length Opsin 1 long‐wave‐sensitive 1 (Opn1lw1) and full‐length Opsin 1 long‐wave‐sensitive 2 (Opn1lw2) under the control of their endogenous promoters. Both fusion proteins are localized in the outer segments of photoreceptor cells. During development, Opn1lw2‐mKate2 is detected from the initial formation of outer segments onward. In contrast, Opn1lw1‐mNeonGreen is first detected in juvenile Zebrafish at about 2 weeks postfertilization, and both opsins continue to be expressed throughout adulthood. It is important to note that the presence of the transgene did not significantly alter the size of outer segments.Conclusions: We have generated a transgenic line that mimics the endogenous expression pattern of Opn1lw1 and Opn1lw2 in the developing and adult retina. In contrast to existing lines, our transgene design allows to follow protein localization. Hence, we expect that these lines could act as useful real‐time reporters to directly measure phenomena in retinal development and disease models. Developmental Dynamics 247:951–959, 2018 . © 2018 The Authors Developmental Dynamics published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists Key Findings: We have generated multiple transgenes that mimic the endogenous expression pattern of the two red opsins, Opn1lw1 and Opn1lw2, in the developing and adult retina. The opsin fusion protein reflects the endogenous proteins dynamics. This line provides a tool for various applications, including the analysis of expression, protein localisation and trafficking and opsin switching.